Peran Pondok Pesantren dalam Membentuk Kemandirian Belajar Santri Brokenhome - Maulana, M. Irsyad; Sobiroh, Novi Ismi (Institut Agama Islam Negeri Kediri, 2024)
Abstract: Islamic boarding schools, as religious-based educational institutions, have an important role in forming the character and independence of students. This research aims to reveal the extent to which Islamic boarding schools can become a